Age and sex differences in prevalence and clinical correlates of depression: first results from the Irish Longitudinal Study on Ageing. - KENNY, ROSE; CRONIN, HILARY; O'REGAN, CLAIRE (My University, 2013)
OBJECTIVE: The risk of depression is increased by physical illness; however, the nature of this relationship is complex and unclear. Here, we explore the prevalence and clinical correlates of depression, with particular emphasis on factors representing consequences or physical manifestations of disease and identify age and gender differences in their effects. METHODS: A population-representative sample of 8175 community-dwelling adults aged 50 years and over participated in the first wave of The Irish Longitudinal Study on Ageing. The primary outcome measure was clinically significant depressive symptoms defined by a score of 16 or greater on the 20-item Centre for Epidemiologic Studies Depression scale. RESULTS: Overall, 10% (95% CI: 9-11%) of adults reported clinically significant depressive symptoms. Physical illness is associated with depressive symptoms only in adults 65 years and older; in adults aged 50-64 years, the association is mediated by medication use, and this age difference is statistically significant (p < 0.00). Irrespective of age, chronic pain and incontinence were stronger predictors of depression in men (interaction effects p < 0.00) CONCLUSIONS: Our findings identify age-specific and gender-specific clinical markers for depression risk among the older population, which may identify those more likely to present with depression in community settings.
PUBLISHED
PMID: 23553681
Keywords: physical illness; correlates; ageing; depression; Ageing